Website Quality Analysis of Balai Besar Pascapanen Bogor Using 2QCV3Q Model - Rinova Budiman; Arif Imam Suroso; Irman Hermadi (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2019)
BB-Pascapanen website is an official website of Balai Besar Pascapanen Bogor whose mission is to be able to integrate information as a research institute producing technology and innovation of agricultural post-harvest that supports the realization of food sovereignty and farmers' welfare. Based on the regulation and to accommodate those missions the website has been developed. The purpose of this study is to analyze the quality of the BB-Pascapanen website through a 2QCV3Q model. This model was chosen because it has a multi-party approach involving three actors in the development of a website, website owner, web developer and user which will make an analysis of website quality management implemented more detail. The results of the analysis show from institution and web developer point of view that the feasibility dimension needs performance improvement. While the other dimensions from user point of view that need to be improved are the dimension of identity (attributes of website uniqueness, Impressum distinctness), content (attribute of information detail and accuracy), services (attribute of correspondence feature), locations (attribute of availability of Link, URL easy to remember, easy searching in website, addresses written in website exists in google map, hotline), and usability (attribute of layout structure, orientation navigation and response, download time).